Acts of Neolithic ritualization associated with Levantine bovine figurines. (3rd July 2018) - Orrelle, Estelle; Kolska Horwitz, Liora
ABSTRACT: This paper investigates a corpus of Neolithic clay bovine figurines recovered from archaeological sites in the Central and Southern Levant. Despite numerous investigations, their function as utilitarian versus ritual objects is still unclear. In order to assess this issue, the depositional contexts and physical characteristics of just over 500 figurines were examined. The results reveal formalized and repetitive contextual data for the majority of the figurines studied, as well as commonality in their form and modifications. With reference to analogues from later Mesopotamian anti-witchcraft texts, support is found for the identification of the bovine figurines as objects associated with acts of ritualization, especially sacrifice, tied to the veneration of aurochs in Pre-Ceramic Neolithic periods. Furthermore, a symbolic structure linking bulls, sun, fire, ash, purification, fertility and rebirth was identified, possibly tying the bovine figurines to later fire rituals that are celebrated worldwide.